THE ROLE OF ISLAMIC BOARDING SCHOOLS IN IMPLEMENTATION OF SHARIA TRANSACTION PRINCIPLES AT BMT AL-ROSYID BERKAH BERSAMA - Izzatul Muna; Khotib Khotib; Muhammad Lathoif Ghozali (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
This study was conducted to reveal descriptively through a qualitative approach about (1) How is the role of Al-Rosyid Islamic Boarding School in the development of BMT, (2) How is the form of the principle of sharia transactions at BMT Al-Rosyid Berkah Bersama, (3) How is the role of Islamic boarding schools in implementing the principle of sharia transactions at BMT Al-Rosyid Berkah Bersama. The research method used is a qualitative method with a field research approach. Qualitative research is carried out in original conditions and is in the form of new findings. The results of the study revealed that; (1) Recruiting several alumni of the Al-Rosyid Islamic boarding school, holding regular evaluations with BMT management to discuss problems and solutions that exist in the movements and activities at BMT Al Rosyid Berkah Bersama, socialize the importance of the sharia financing system to students and the community, participate in efforts to expand corporate wings and participate in fundraising. (2) Implementation of the principle of brotherhood (ukhuwwah), implementation of the principle of Justice ('adÄlah), implementation of the principle of benefit (maá¹£lahah), implementation of the principle of Balance (tawÄzun) and implementation of the principle of Universalism (shumuliyyah). (3) Recruiting and attracting capable alumni in BMT, especially in the field of sharia transaction principles, holding an intensive personal approach to BMT members, preparing future BMT cadres who are good in the field of sharia transaction principles, and several other important roles.